English skills, earnings, and the occupational sorting of Mexican Americans along the U.S.-Mexico border - Davila, A.; Mora, M. T.
tbls.
pp. 133-157
Keywords: Inmigrantes; Siglo XX; Estados Unidos de America; Mexico; Fronteras; Ingresos; Aspectos Economicos; Formación Profesional